Polyester Film

The polyester film with specific particle sizes and concentrations on both sides, along with a separate layer, addresses the issues of matte finish and curling, providing enhanced adhesion and visibility during transfer.

JP7622777B2Active Publication Date: 2025-01-28MITSUBISHI CHEM CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023083665
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-02-27
Filing Date
2023-05-22
Publication Date
2025-01-28
Estimated Expiration
2039-02-27

AI Technical Summary

Technical Problem

Existing polyester films used for transferring a matte appearance often result in a smoothed surface when a separate layer is formed, failing to achieve the expected matte finish and exhibit poor handling properties with curling issues.

Method used

A polyester film with a particle-containing layer having particles with an average size of 2.0 μm or more and a transparent concentration OD value of 0.25 or more, along with a separate layer on one or both sides, enhances the matte finish and prevents curling by using different particle sizes and concentrations on each side.

Benefits of technology

The film achieves an excellent matte finish and improved handling properties by maintaining a rough surface state during transfer, ensuring adhesion and preventing curling, while maintaining visibility and ease of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622777000004
    Figure 0007622777000004
  • Figure 0007622777000001
    Figure 0007622777000001
  • Figure 0007622777000002
    Figure 0007622777000002
Patent Text Reader

Abstract

To provide a novel polyester film excellent in visibility, in other words distinctive nature, of a polyester film when transferring, and yet capable of imparting contemplated matt feeling to an object without smoothing a rough surface state if a release layer is formed concerning a polyester film having a roughened film surface, and used for a use application of transferring a surface state thereof.SOLUTION: A polyester film is constituted by forming a release layer on a surface of the particle-containing layer of a polyester film substrate provided with a particle-containing layer containing a particle having an average particle size of 2.0 μm or more where the transmission density OD value is 0.10 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film with releasability that can transfer a matte appearance. [Background technology]

[0002] Polyester films, typified by polyethylene terephthalate and polyethylene naphthalate, have excellent properties such as mechanical strength, dimensional stability, flatness, heat resistance, chemical resistance, optical properties, etc., and are also excellent in cost performance, and therefore are used for various purposes.

[0003] One example of the use of polyester films is their use as electromagnetic shielding. In plasma displays (PDPs) and the like, an electromagnetic shielding film, i.e., a conductive film, is attached to the front of the display panel, and a conductive film made of polyester film with a mesh-like metal wire is generally used as this electromagnetic shielding film.

[0004] This type of electromagnetic wave shielding film is formed on a support film, and then the film is pressed at high temperature onto the surface of various devices to transfer the electromagnetic wave shielding film. Conventionally, a flat polyester film has generally been used as the support film for such a transfer-type electromagnetic shielding film, but in order to give the product a matte appearance, it has been proposed to use a polyester film with a matte surface as the support film and transfer this matte surface to the product.

[0005] For example, Patent Document 1 discloses a biaxially oriented release polyester film, which has a polyester A layer as the outermost layer of a base film, the polyester A layer containing inorganic particles and / or organic particles in an amount of 0.1% by mass to 10% by mass, with the entire polyester A layer being 100% by mass, and a coating layer containing a melamine resin as a main component laminated on the A layer, and the gloss level of the surface on which the coating layer is laminated is 30 or less.

[0006] Patent Document 2 discloses a biaxially oriented polyester film that is a laminated polyester film having a base layer and a particle-containing matte layer on at least one surface, the matte layer surface having an average surface roughness (Ra) of 400 to 1000 nm, a 10-point average roughness (Rz) of 4000 to 8000 nm, a glossiness (G60) of 6 to 20, and a void breaking rate of protrusions on the surface of 20% or less.

[0007] Patent Document 3 discloses a biaxially oriented polyester film for release use, which has a polyester A layer containing inorganic particles and / or organic particles as at least one outermost layer, the average surface roughness Ra of the outermost polyester A layer surface being 0.38 μm or more and 1.0 μm or less, and the average length RSm of the roughness curve element of the polyester A layer surface being 10 μm or more and 80 μm or less. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2015-66805 A [Patent Document 2] JP 2016-97522 A [Patent Document 3] JP 2016-175229 A Summary of the Invention [Problem to be solved by the invention]

[0009] As described above, by roughening the surface of a polyester film to give it a matte finish, the surface of the polyester film can be brought into contact with the surface of an object and pressed to adhere thereto, and then the polyester film can be peeled off, thereby transferring the roughened surface state to the surface of the object and giving it a matte appearance.

[0010] Previously proposed transfer polyester films of this type required the formation of a separate release layer by laminating a release film on the surface of the polyester film or by applying a release agent, and when the release layer was formed, the roughened state of the polyester film surface was smoothed out, making it impossible to impart the desired matte finish to the surface of the target object. Furthermore, a polyester film having releasability is also expected to have excellent visibility, in other words, distinguishability.

[0011] Therefore, the first object of the present invention is to provide a new polyester film which has a roughened film surface and is used for applications in which the surface condition is transferred, and which has excellent visibility, in other words, distinguishability, of the polyester film during transfer, and which, even when a release layer is formed, does not smooth out the roughened surface, and can impart the desired matte feel to the object. A second object of the present invention is to provide a new polyester film which can prevent curling (rolling tendency) of the entire polyester film, while improving handleability and further improving adhesion to products to which the polyester film is laminated. [Means for solving the problem]

[0012] In order to achieve the above-mentioned first object, the present invention proposes a first polyester film, which is characterized by having a polyester film base with a particle-containing layer containing particles having an average particle size of 2.0 μm or more, and having a transmission density OD value of 0.25 or more. In order to achieve the above-mentioned first object, the present invention also proposes a second polyester film comprising a polyester film substrate having a particle-containing layer containing particles having an average particle size of 2.0 μm or more, and a release layer formed on the surface of the particle-containing layer, and characterized in that the transmission density OD value is 0.10 or more.

[0013] In order to achieve the second object, the present invention proposes a third polyester film having a polyester film base provided with a particle-containing layer A containing particles having an average particle size of 2.0 μm or more on one side of the base layer, and a particle-containing layer B containing particles having an average particle size of 2.0 μm or more on the other side of the base layer, wherein the content of particles having an average particle size of 2.0 μm or more is lower in particle-containing layer B than in particle-containing layer A. Effect of the Invention

[0014] The first and second polyester films proposed by the present invention can be provided with a release layer, so that the roughened state of the polyester film surface is not smoothed when the release layer is formed, and the desired matte feel can be imparted to the object. In addition, since the transmission density OD value of the polyester film is 0.10 or more or 0.25 or more, the visibility of the polyester film during transfer, in other words, the distinguishability, is excellent.

[0015] The third polyester film proposed by the present invention has a polyester film base material with particle-containing layers A and B on both sides of the base layer, and the content of particles with an average particle size of 2.0 μm or more is smaller in particle-containing layer B than in particle-containing layer A. Since the particle-containing layers A and B are provided on both sides of the base layer, curling of the entire polyester film can be prevented. Moreover, while the surface side of the particle-containing layer A imparts a matte feel to the surface of the object, the particle-containing layer B has a particle content smaller than that of the particle-containing layer A, so that the surface processing suitability can be ensured and it is easy to laminate a desired layer on the surface of the particle-containing layer B, so that, for example, the adhesion with the product to be laminated can be improved. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the configuration of a polyester film according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.

[0018] <<This polyester film 1>> A polyester film according to one embodiment of the present invention (referred to as "polyester film 1") is a polyester film provided with a particle-containing layer A that contains particles having an average particle size of 2.0 μm or more. The polyester film 1 may be a non-stretched film (sheet) or a stretched film. Of these, a uniaxially or biaxially stretched film is preferred. Of these, a biaxially stretched film is preferred from the viewpoints of excellent balance of mechanical properties and flatness. The polyester film 1 may consist of only a polyester film provided with a particle-containing layer A containing particles having an average particle size of 2.0 μm or more, or may be formed by laminating other layers on the polyester film.

[0019] <<This polyester film 10>> A polyester film according to another embodiment of the present invention (referred to as "polyester film 10") is a polyester film having a configuration in which a release layer is formed on one or both sides of a polyester film substrate.

[0020] The laminated structure of the polyester film 10 may be a structure in which a release layer is formed on one side of a polyester film substrate and the surface of the polyester film substrate is left as is on the other side, or a structure in which another layer is formed on the other side. Also, a structure in which release layers are formed on both sides of a polyester film substrate may be used. Furthermore, another layer may be provided between the polyester film substrate and the release layer. However, the release layer is preferably the outermost surface of at least one of the substrates.

[0021] <Polyester film substrate> The polyester film substrate is preferably provided with a particle-containing layer A containing particles having an average particle size of 2.0 μm or more. That is, it is preferable to use the present polyester film 1 as the polyester film substrate. Therefore, the following description of the polyester film substrate also includes the description of the present polyester film 1.

[0022] The polyester film substrate may be configured to consist of only the particle-containing layer A, or may have the particle-containing layer A on one or both sides of the substrate layer. Specific examples of the latter include a substrate having the particle-containing layer A on both sides of the substrate layer, a substrate having the particle-containing layer A on one side of the substrate layer and a particle-containing layer B different from the particle-containing layer A formed on the other side of the substrate layer, a substrate having the particle-containing layer A on one side of the substrate layer and no layer formed on the other side of the substrate layer, or a substrate having the particle-containing layer A on one side of the substrate layer and a layer not containing particles formed on the other side of the substrate layer. In particular, a polyester film substrate having a particle-containing layer A on one side of the substrate layer and a particle-containing layer B different from the particle-containing layer A formed on the other side of the substrate layer is preferred, and this configuration will be described in detail later.

[0023] The polyester film substrate preferably has a transmission density OD value of 0.10 or more. A transmission density OD value of 0.10 or more means high opacity, in other words, high whiteness, and the whiteness is greater. From this viewpoint, it is more preferably 0.10 to 1.0, and among these, it is more preferably 0.15 or more or 0.90 or less, and among these, it is even more preferably 0.20 or more or 0.80 or less, and among these, it is even more preferably 0.25 or more. If the transmission density OD value of the polyester film substrate is within the above range, the visibility, in other words, the distinguishability is good, so that the polyester film 10 can be easily peeled off after the rough surface is transferred to the transfer target.

[0024] Methods for making the transmission density OD value of the polyester film substrate 0.10 or more can be known, such as adding a white pigment, adding a material with a large refractive index difference from the main component resin of the substrate, or stretching a film containing fine particles to form voids in the film substrate. Among them, when whitening is achieved by including a white pigment, for example, metal compound particles, the whitening can be achieved by including metal compound particles in any one or more of the substrate layer, the particle-containing layer, and the layer provided on the opposite side of the substrate layer to the particle-containing layer. In this case, the white pigment can be exemplified by particles Y having an average particle size of less than 2.0 μm, which will be described later. It goes without saying that the transmission density OD value of the polyester film 10 is lower than the transmission density OD value of the polyester film substrate.

[0025] (Polyester as the main resin component of each layer) The layers constituting the polyester film substrate, for example the above-mentioned substrate layer, particle-containing layer A, particle-containing layer B and further other layers, are preferably layers containing polyester as a main component resin. Here, the term "main component resin" refers to the resin that is contained in the largest proportion among the resin components that constitute each layer.

[0026] The polyester may be any polyester obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and examples of the other aliphatic glycol include ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol.

[0027] The polyester may be a homopolyester or a copolymer polyester. The dicarboxylic acid component of the copolymer polyester may be, for example, one or more selected from isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, adipic acid, sebacic acid, and oxycarboxylic acid, and the other glycol component may be, for example, one or more selected from ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, and neopentyl glycol. From the viewpoint of effectively imparting a matte feel, it is preferable that the third component contained is isophthalic acid. The copolymer polyester preferably contains a third component in an amount of 30 mol % or less, more preferably 5 mol % or more or 30 mol % or less, even more preferably 25 mol % or less, and even more preferably 7 mol % or more or 22 mol % or less. By being in this range, it is possible to effectively impart a matte feel while maintaining film formation stability.

[0028] Representative examples of polyester include polyethylene terephthalate (PET) and polyethylene-2,6-naphthalenedicarboxylate (PEN).

[0029] (base material layer) The base layer of the polyester film base is the thickest layer among the layers constituting the polyester film base, and its composition is arbitrary so long as it contains the above-mentioned polyester as the main component resin.

[0030] The base layer may include a layer containing particles, or may consist of only a layer containing particles, although from the viewpoint of cost, it is preferable that the base layer is a layer that does not contain particles such as organic particles or inorganic particles described below.

[0031] From the viewpoint of preventing curling of the polyester film 10, the thickness of the base material layer is preferably 60 to 99% of the thickness of the polyester film base material, more preferably 65% ​​or more or 99% or less, and even more preferably 70% or more or 99% or less. When the thickness is in this range, the base material layer itself has stiffness, so that the polyester film 10 is less likely to curl.

[0032] (Particle-containing layer A) The particle-containing layer A is a layer containing particles X having an average particle size of 2.0 μm or more, and it is preferable that a release layer, which will be described later, is provided on the surface of the layer.

[0033] The particles X contained in the particle-containing layer A preferably have an average particle size of 2.0 μm or more. By containing particles X having an average particle size of 2.0 μm or more in the particle-containing layer A, the surface of the particle-containing layer A can be roughened and made matte. However, if the particles X are too large, the pressure rise in the filter in the polyester extrusion process during film production may increase, reducing productivity, and the particles X may fall off from the particle-containing layer A. Therefore, the average particle size of the particles X is preferably 2.0 μm or more, and more preferably 10.0 μm or less, and even more preferably 3.0 μm or more or 9.0 μm or less, and even more preferably 4.0 μm or more or 8.0 μm or less.

[0034] In addition, when the particles are powder, the average particle size of the particles X can be the particle size (d50) at an accumulated volume fraction of 50% in the equivalent sphericity distribution measured by a centrifugal sedimentation type particle size distribution measuring device (e.g., SA-CP3 type, manufactured by Shimadzu Corporation). The average particle size of the particles in the film or layer can be determined by observing 10 or more particles X with a scanning electron microscope (SEM) to measure the diameters of the particles X and taking the average value. In this case, in the case of non-spherical particles, the average value of the longest diameter and the shortest diameter can be measured as the diameter of each particle X. The same applies to the particles Y described below.

[0035] The shape of the particles X is arbitrary. For example, it may be any of spherical, blocky, rod-like, flat, etc. However, from the viewpoint of obtaining a uniform matte surface, a spherical shape is preferable. There are no particular limitations on the hardness, specific gravity, color, etc. of the particles X, and two or more different types may be used in combination.

[0036] The particles X having an average particle size of 2.0 μm or more are not particularly limited as long as they are particles capable of imparting a matte finish, and may be, for example, inorganic particles, organic particles, or crosslinked polymer particles. Inorganic particles are preferred from the viewpoint that they may form voids in the film when stretched, making it unnecessary to add a white pigment to improve visibility, while organic particles are preferred from the viewpoint that they are less likely to form voids, and therefore do not reduce the strength of the film.

[0037] Examples of inorganic particles include silica, calcium carbonate, kaolin, talc, magnesium carbonate, barium carbonate, calcium sulfate, barium sulfate, lithium phosphate, calcium phosphate, magnesium phosphate, aluminum oxide, titanium oxide, zirconium oxide, lithium fluoride, calcium fluoride, lithium fluoride, zeolite, and molybdenum sulfide. The silica particles may contain, for example, hydrous silicon dioxide in addition to silicon dioxide (SiO2).

[0038] Examples of organic particles include acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. Among these, particles made of a resin containing methyl methacrylate or styrene or both as copolymerization components are preferred because they are particularly compatible with PET films.

[0039] Examples of the crosslinked polymer particles include homopolymers or copolymers of vinyl monomers such as divinylbenzene, styrene, acrylic acid, methacrylic acid, acrylic acid or methacrylic acid. Other crosslinked polymer particles such as polytetrafluoroethylene, benzoguanamine resin, thermosetting epoxy resin, unsaturated polyester resin, thermosetting urea resin, and thermosetting phenolic resin may also be used.

[0040] The content of particles X in the particle-containing layer A is preferably 0.1 to 20% by mass, from the viewpoint of suitably roughening the surface of the particle-containing layer A and preventing breakage or the like during film stretching, and is more preferably 1% by mass or more or 18% by mass or less, more preferably 2% by mass or more or 15% by mass or less, and even more preferably 3% by mass or more or 10% by mass or less. The particle-containing layer A may also contain particles Y, which will be described later.

[0041] The thickness of the particle-containing layer A is preferably 1.0 to 20 μm, more preferably 2.0 μm or more or 20 μm or less, even more preferably 3.0 μm or more or 20 μm or less, and even more preferably 4.0 μm or more or 15 μm or less. By making the thickness of the particle-containing layer A 1.0 μm or more, a matte finish can be effectively imparted. On the other hand, if the thickness of the particle-containing layer A exceeds 20 μm, the effect of improving the matte finish is reduced, and there is a risk that the roughening of the film surface caused by the particles X may be reduced.

[0042] With regard to the relationship between the thickness of the particle-containing layer A and the average particle size of the particles X, from the viewpoint of roughening the film surface and suppressing particle dropout, (average particle size of the particles X) / (thickness of the particle-containing layer A) is preferably 0.1 or more and 5.0 or less, more preferably 0.3 or more and 4.0 or less, and particularly preferably 0.5 or more and 3.0 or less.

[0043] (Particle-containing layer B) As described above, the base layer may have a particle-containing layer A on one side thereof, and a particle-containing layer B different from the particle-containing layer A may be formed on the other side thereof. A release layer, which will be described later, does not need to be provided on the surface of the particle-containing layer B, but this does not exclude a configuration in which a release layer is provided.

[0044] In terms of preventing curling of the entire polyester film 10, it is preferable that the particle-containing layer B also contains particles X having an average particle size of 2.0 μm or more. However, the surface of the particle-containing layer B only needs to be roughened to an extent that makes it easy to handle, and does not need to be as rough as the surface of the particle-containing layer A. Therefore, the content of particles X having an average particle size of 2.0 μm or more may be less than that of the particle-containing layer A. Since the content of particles X having an average particle size of 2.0 μm or more is less in the particle-containing layer B than in the particle-containing layer A, curling of the entire polyester film 10 can be prevented, a matte feel is imparted to the surface of the object on the surface side of the particle-containing layer A, and a desired layer can be easily laminated on the surface of the particle-containing layer B. Specifically, the content (mass%) of particles X contained in particle-containing layer B is preferably 0.1 to 100% of the content (mass%) of particles X contained in particle-containing layer A, and is more preferably 1% or more or 95% or less, more preferably 5% or more or 90% or less, and is even more preferably 10% or more or 80% or less, and even more preferably 60% or less.

[0045] The particle-containing layer B may contain particles Y having an average particle size of less than 2.0 μm in order to whiten the polyester film 10 . In this case, the particle-containing layer B may contain particles Y without containing particles X, or may contain particles Y together with particles X. When particles Y are contained together with particles X, the mass ratio of particles X to particles Y is preferably 1:99 to 99:1, more preferably 10:90 to 90:10, and even more preferably 15:85 to 85:15.

[0046] The shape of the particles Y is arbitrary. For example, it may be any of spherical, blocky, rod-like, flat, etc. However, from the viewpoint of preventing the formation of coarse protrusions due to aggregation, the particles Y are preferably spherical. There are no particular limitations on the hardness, specific gravity, color, etc. of the particles Y, and two or more different types may be used in combination.

[0047] From the viewpoint of imparting white opacity through a light scattering effect, the average particle size of the particles Y is preferably 0.05 μm to 0.50 μm, more preferably 0.10 μm or more or 0.45 μm or less, even more preferably 0.20 μm or more or 0.40 μm or less, and even more preferably 0.25 μm or more.

[0048] The particles Y are preferably metal compound particles from the viewpoint of imparting white opacity through a light scattering effect. Examples of metal compound particles include titanium oxide, calcium carbonate, barium sulfate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, zirconium oxide, and the like. Among these, metal compound particles such as titanium oxide, calcium carbonate, and barium sulfate can be mentioned. In addition, in particle-containing layer B, when the particles corresponding to particle X and the particles corresponding to particle Y are made of the same material, they are separate particles with different average particle diameters as raw materials, but when mixed (blended), they become nothing more than a single type of particle with an average particle diameter between the two. In such a case, the average particle diameter after mixing is used to recognize it as either particle X or particle Y.

[0049] The thickness of the particle-containing layer B is preferably in the same range as that of the particle-containing layer A, from the viewpoint of preventing curling of the polyester film 10. From this viewpoint, the thickness of the particle-containing layer B is also preferably 1.0 to 20 μm, and more preferably 2.0 μm or more or 18 μm or less, more preferably 3.0 μm or more or 17 μm or less, and even more preferably 4.0 μm or more or 15 μm or less.

[0050] From the viewpoint of preventing curling of the polyester film 10, the thickness ratio of the particle-containing layer A to the particle-containing layer B, (thickness of the particle-containing layer A) / (thickness of the particle-containing layer B), is preferably 0.1 or more and 10 or less, more preferably 0.2 or more or 5.0 or less, and particularly preferably 0.5 or more or 2.0 or less.

[0051] (Other Ingredients) Each layer constituting the polyester film base may contain, as necessary, a conventionally known weathering agent, light resistance agent, light shielding agent, antioxidant, heat stabilizer, lubricant, antistatic agent, fluorescent brightener, dye, pigment, etc. Depending on the application, an ultraviolet absorbing agent, particularly a benzoxazinone ultraviolet absorbing agent, may be contained.

[0052] <Release layer> The polyester film 10 preferably has a structure in which a release layer is formed on the surface of the particle-containing layer A of a polyester film substrate.

[0053] The release layer preferably has a crosslinked structure derived from a crosslinking agent, and has excellent hardness so that the polyester film 10 can withstand pressure when pressed against an object.

[0054] The thickness of the release layer is preferably 0.001 to 1 μm, from the viewpoint of having releasability while not smoothing (reducing) the roughness of the surface of the polyester film substrate, and more preferably 0.002 μm or more or 0.5 μm or less, more preferably 0.005 μm or more or 0.2 μm or less, more preferably 0.008 μm or more or 0.15 μm or less, more preferably 0.01 μm or more or 0.1 μm or less, and even more preferably 0.01 μm or more or 0.08 μm or less. The thickness of the release layer is preferably 0.1 to 100%, particularly 0.2% or more or 50% or less, and particularly 1.0% or more or 25% or less, of the average surface roughness (Ra) of the surface on which the release layer is provided.

[0055] (Formation of release layer) The release layer is preferably provided as an extremely thin film on the surface of the particle-containing layer A, i.e., the roughened surface, and is therefore preferably formed by employing a coating and stretching method (in-line coating). However, the method is not limited to this method.

[0056] As a coating and stretching method, for example, in the case of sequential biaxial stretching, it is preferable to coat the surface of the particle-containing layer A with the "release layer-forming composition" after the first stage of stretching is completed and before the second stage of stretching. In this way, coating is possible simultaneously with stretching, and the thickness of the release layer can be made thin according to the stretching ratio, so that a film suitable as a polyester film can be produced.

[0057] Examples of a method for applying a coating liquid comprising a release layer-forming composition include air doctor coating, blade coating, rod coating, bar coating, knife coating, squeeze coating, impregnation coating, reverse roll coating, transfer roll coating, gravure coating, kiss roll coating, cast coating, spray coating, curtain coating, calendar coating, and extrusion coating.

[0058] More specifically, for example, in the case of successive biaxial stretching, a method in which a coating liquid consisting of a release layer-forming composition is coated on a uniaxially stretched film that has been particularly stretched in the longitudinal direction (machine direction), and then the film is stretched in the transverse direction to form a polyester film is excellent. According to this method, since the polyester film and the release layer can be formed simultaneously, there is an advantage in terms of production costs, and since stretching is performed after coating, the thickness of the release layer can be changed by the stretching ratio, and thin film coating can be performed more easily than offline coating.

[0059] In addition, by providing a release layer on the polyester film before stretching, the release layer can be stretched together with the polyester film, and the release layer can be firmly attached to the polyester film. Furthermore, in the production of biaxially stretched polyester films, the film can be restrained in the longitudinal and lateral directions by stretching while holding the film ends with clips or the like, and high temperatures can be applied in the heat setting step while maintaining the flatness without wrinkles or the like. Therefore, the heat treatment performed after coating can be performed at a high temperature that cannot be achieved by other methods, which improves the film-forming properties of the release layer and enables the release layer and polyester film to adhere more firmly to each other, thereby resulting in a stronger release layer.

[0060] Regardless of whether the release layer is formed by off-line coating or in-line coating, a heat treatment and irradiation with active energy rays such as ultraviolet light may be used in combination as necessary. In order to improve the coatability and adhesiveness of the coating solution for forming the release layer to the polyester film, the polyester film may be subjected to a surface treatment such as a chemical treatment, corona discharge treatment, plasma treatment, ozone treatment, chemical treatment, or solvent treatment before coating.

[0061] The release layer-forming composition, i.e., the coating liquid, may be a resin composition containing a release agent and a binder.

[0062] The "release agent" to be incorporated in the release layer-forming composition is not particularly limited, and any conventionally known release agent can be used. Examples of the release agent include long-chain alkyl group-containing compounds, fluorine compounds, silicone compounds, waxes, etc. Among these, compounds containing long-chain alkyl groups and waxes are preferred from the viewpoint of low possibility of contamination when applied to optical applications, and waxes are preferred from the viewpoint of not significantly decreasing releasability even when heated.

[0063] The wax may be a natural wax, a synthetic wax, or a modified wax. Natural waxes include vegetable waxes, animal waxes, mineral waxes, and petroleum waxes. Examples of vegetable waxes include candelilla wax, carnauba wax, rice wax, wood wax, jojoba oil, and the like. Examples of animal waxes include beeswax, lanolin, spermaceti, etc. Examples of mineral waxes include montan wax, ozokerite, ceresin, etc. Examples of the petroleum wax include paraffin wax, microcrystalline wax, and petrolatum.

[0064] Examples of synthetic waxes include synthetic hydrocarbons, modified waxes, hydrogenated waxes, fatty acids, acid amides, amines, imides, esters, ketones, Fischer-Tropsch wax (also known as Sasol wax), polyethylene wax, etc. In addition, the following polymers, which are relatively low molecular weight polymers (specifically, polymers with number average molecular weights of 500 to 20,000), can be mentioned: polypropylene, ethylene-acrylic acid copolymers, polyethylene glycol, polypropylene glycol, block or graft bond of polyethylene glycol and polypropylene glycol, etc.

[0065] Examples of modified waxes include montan wax derivatives, paraffin wax derivatives, and microcrystalline wax derivatives. The derivatives are compounds obtained by any of the following processes: refining, oxidation, esterification, and saponification, or a combination thereof. Examples of hydrogenated waxes include hydrogenated castor oil and hydrogenated castor oil derivatives.

[0066] Among these, from the viewpoint of stabilizing blocking properties and the like, the release agent in the release layer is preferably a synthetic wax, more preferably a polyethylene wax, and even more preferably an oxidized polyethylene wax. The number average molecular weight of the synthetic wax is usually 500 to 30,000, preferably 1,000 to 15,000, and more preferably 2,000 to 8,000, from the viewpoints of stability of properties such as blocking and ease of handling.

[0067] In addition, when the release layer is formed, taking into consideration the fact that heating is performed for crosslinking, etc., among the above waxes, those having a melting point or softening point of 80° C. or higher, particularly 110° C. or higher, are preferred. There is no upper limit for the melting point or softening point of the wax, and it is usually 300° C. or lower.

[0068] The proportion of the release agent in the release layer forming composition is preferably 1 to 50 mass % of the non-volatile components, more preferably 5 mass % or more or 40 mass % or less, and even more preferably 10 mass % or more or 30 mass % or less. By setting the ratio of the release agent in the release layer-forming composition within the above range, it is possible to increase the coating strength while maintaining good releasability.

[0069] In order to increase the strength of the release layer and further improve wettability, it is preferable that the release layer-forming composition contains a crosslinking agent. When the release layer-forming composition contains a crosslinking agent, the release layer after formation has a crosslinked structure derived from the crosslinking agent. In order to increase the strength of the release layer and further to improve the adhesion between the polyester film substrate and the release layer, it is preferable that the release layer-forming composition contains a binder.

[0070] As the crosslinking agent, a conventionally known material can be used. For example, oxazoline compounds, isocyanate compounds, epoxy compounds, melamine compounds, carbodiimide compounds, silane coupling compounds, hydrazide compounds, aziridine compounds, etc. can be mentioned. Among them, oxazoline compounds, isocyanate compounds, epoxy compounds, melamine compounds, carbodiimide compounds, and silane coupling compounds are preferred. In order to further strengthen the strength of the release layer, melamine compounds and oxazoline compounds are preferred, and in order to improve the adhesion to the substrate film, oxazoline compounds, isocyanate compounds, epoxy compounds, and carbodiimide compounds are preferred, and oxazoline compounds and isocyanate compounds are particularly preferred.

[0071] Specific examples of the binder include acrylic resins, polyvinyls (polyvinyl alcohol, vinyl chloride-vinyl acetate copolymers, etc.), polyester resins, urethane resins, polyalkylene glycols, polyalkyleneimines, methyl cellulose, hydroxy cellulose, starches, etc. Among these, polyester resins are preferred from the viewpoint of improving the adhesion between the polyester film substrate and the release layer.

[0072] The acrylic resin is a polymer made of polymerizable monomers including acrylic and methacrylic monomers. These may be homopolymers or copolymers, or copolymers with polymerizable monomers other than acrylic and methacrylic monomers. Also included are copolymers of these polymers with other polymers (e.g. polyester, polyurethane, etc.). For example, block copolymers and graft copolymers. Alternatively, polymers (or mixtures of polymers in some cases) obtained by polymerizing polymerizable monomers in a polyester solution or polyester dispersion are also included. Similarly, polymers (or mixtures of polymers in some cases) obtained by polymerizing polymerizable monomers in a polyurethane solution or polyurethane dispersion are also included. Similarly, polymers (or mixtures of polymers in some cases) obtained by polymerizing polymerizable monomers in other polymer solutions or dispersions are also included. In addition, it is possible to contain a hydroxyl group or an amino group in order to further improve adhesion to the substrate.

[0073] The polymerizable monomer is not particularly limited, but particularly representative compounds include various carboxyl group-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, and citraconic acid, and salts thereof; various hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, monobutyl hydroxyl fumarate, and monobutyl hydroxy itaconate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, lauryl (meth)acrylate, and the like. p) Various (meth)acrylic acid esters such as acrylates; various nitrogen-containing compounds such as (meth)acrylamide, diacetone acrylamide, N-methylol acrylamide, or (meth)acrylonitrile; various styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, and vinyl toluene; various vinyl esters such as vinyl propionate; various silicon-containing polymerizable monomers such as γ-methacryloxypropyltrimethoxysilane and vinyltrimethoxysilane; phosphorus-containing vinyl monomers; various vinyl halides such as vinyl chloride and vinylidene chloride; and various conjugated dienes such as butadiene.

[0074] When the acrylic resin contains a hydroxyl group, the hydroxyl value of the acrylic resin is preferably 2 to 100 mgKOH / g, more preferably 5 to 50 mgKOH / g. When the hydroxyl value is within the above range, the coating appearance and transparency are improved.

[0075] The polyvinyl alcohol is a compound having a polyvinyl alcohol moiety, and for example, conventionally known polyvinyl alcohols can be used, including modified compounds in which polyvinyl alcohol is partially acetalized or butyralized. The degree of polymerization of polyvinyl alcohol is not particularly limited, but is usually 100 or more, preferably in the range of 300 to 40,000. If the degree of polymerization is less than 100, the water resistance of the release layer may decrease. In addition, the degree of saponification of polyvinyl alcohol is not particularly limited, but a polyvinyl acetate saponification product having a degree of saponification of usually 70 mol % or more, preferably in the range of 70 to 99.9 mol %, more preferably 80 to 97 mol %, and particularly preferably 86 to 95 mol % is practically used.

[0076] The polyester resin may be composed of, for example, the following polyvalent carboxylic acid and polyvalent hydroxy compound as main components. That is, as the polyvalent carboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, trimellitic acid monopotassium salt, and ester-forming derivatives thereof may be used, and as the polyvalent hydroxy compound, Examples of the usable compounds include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate. One or more of these compounds may be appropriately selected and a polyester resin may be synthesized by a conventional polycondensation reaction.

[0077] The urethane resin is a polymeric compound having a urethane bond in the molecule. Usually, the urethane resin is produced by the reaction of a polyol with an isocyanate. Examples of the polyol include polycarbonate polyols, polyester polyols, polyether polyols, polyolefin polyols, and acrylic polyols. These compounds may be used alone or in combination.

[0078] The polycarbonate polyols are obtained by dealcoholization reaction between polyhydric alcohols and carbonate compounds. Examples of polyhydric alcohols include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, and 3,3-dimethylolheptane. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, etc., and examples of polycarbonate-based polyols obtained by the reaction of these compounds include poly(1,6-hexylene) carbonate, poly(3-methyl-1,5-pentylene) carbonate, etc.

[0079] The polyester polyols include polycarboxylic acids (malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.) or their acid anhydrides and polyhydric alcohols (ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2 ... methyl-2,4-pentanediol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, lactonediols, etc.

[0080] Examples of the polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene ether glycol, and polyhexamethylene ether glycol.

[0081] Examples of polyisocyanate compounds used to obtain urethane resins include aromatic diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylene diphenyl diisocyanate, phenylene diisocyanate, naphthalene diisocyanate, and tolidine diisocyanate, aliphatic diisocyanates having an aromatic ring such as α,α,α',α'-tetramethyl xylylene diisocyanate, aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate, and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and isopropylidenedicyclohexyl diisocyanate. These may be used alone or in combination.

[0082] A chain extender may be used when synthesizing the urethane resin. The chain extender is not particularly limited as long as it has two or more active groups that react with an isocyanate group, and generally, a chain extender having two hydroxyl groups or two amino groups can be mainly used.

[0083] Examples of chain extenders having two hydroxyl groups include glycols such as aliphatic glycols, such as ethylene glycol, propylene glycol, and butanediol; aromatic glycols, such as xylylene glycol and bishydroxyethoxybenzene; and ester glycols, such as neopentyl glycol hydroxypivalate. Examples of chain extenders having two amino groups include aromatic diamines such as tolylenediamine, xylylenediamine, and diphenylmethanediamine; aliphatic diamines such as ethylenediamine, propylenediamine, hexanediamine, 2,2-dimethyl-1,3-propanediamine, 2-methyl-1,5-pentanediamine, trimethylhexanediamine, 2-butyl-2-ethyl-1,5-pentanediamine, 1,8-octanediamine, 1,9-nonanediamine, and 1,10-decanediamine; and alicyclic diamines such as 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, dicyclohexylmethanediamine, isopropylidenecyclohexyl-4,4'-diamine, 1,4-diaminocyclohexane, and 1,3-bisaminomethylcyclohexane.

[0084] The urethane resin in the present invention may be one that uses a solvent as a medium, but is preferably one that uses water as a medium. To disperse or dissolve the urethane resin in water, there are a forced emulsification type that uses an emulsifier, a self-emulsification type that introduces a hydrophilic group into the urethane resin, or a water-soluble type. In particular, a self-emulsification type that introduces an ionic group into the structure of the urethane resin to form an ionomer is preferable because it has excellent storage stability of the liquid and excellent water resistance and transparency of the resulting release layer.

[0085] The ionic group to be introduced may be a carboxyl group, a sulfonic acid group, a phosphoric acid group, a phosphonic acid group, a quaternary ammonium salt, or the like, with the carboxyl group being preferred. Various methods can be used to introduce a carboxyl group into the urethane resin at each stage of the polymerization reaction.

[0086] For example, there is a method of using a resin having a carboxyl group as a copolymerization component during synthesis of a prepolymer, or a method of using a component having a carboxyl group as one component of a polyol, polyisocyanate, chain extender, etc. In particular, a method of using a carboxyl group-containing diol and introducing a desired amount of carboxyl groups by the amount of this component is preferred. For example, dimethylolpropionic acid, dimethylolbutanoic acid, bis-(2-hydroxyethyl)propionic acid, bis-(2-hydroxyethyl)butanoic acid, etc. can be copolymerized with the diol used in polymerization of the urethane resin. In addition, it is preferable that the carboxyl group is neutralized with ammonia, amine, alkali metals, inorganic alkalis, etc. to form a salt. Particularly preferred are ammonia, trimethylamine, and triethylamine. In such a polyurethane resin, the carboxyl group from which the neutralizer is removed in the drying process after coating can be used as a crosslinking reaction point with another crosslinking agent. This makes it possible to achieve excellent stability in the liquid state before coating, and to further improve the durability, solvent resistance, water resistance, blocking resistance, etc. of the resulting release layer.

[0087] The proportion of the binder in the release layer forming composition is preferably 20 to 70 mass % of the non-volatile components, more preferably 30 mass % or more or 65 mass % or less, and even more preferably 40 mass % or more or 60 mass % or less. The proportion of the crosslinking agent in the non-volatile components is preferably 10 to 70 mass %, more preferably 15 mass % or more or 60 mass % or less, and even more preferably 20 mass % or more or 40 mass % or less.

[0088] The coating liquid comprising the release layer-forming composition may be an aqueous coating liquid containing water as a solvent or an organic solvent as a main component, but is preferably an aqueous coating liquid. The aqueous coating liquid may contain a small amount of an organic solvent. Examples of the organic solvent include alcohols such as ethanol, isopropanol, ethylene glycol, and glycerin; ethers such as ethyl cellosolve, t-butyl cellosolve, propylene glycol monomethyl ether, and tetrahydrofuran; ketones such as acetone and methyl ethyl ketone; esters such as ethyl acetate; and amines such as methylethanolamine. These can be used alone or in combination. By appropriately selecting and adding these organic solvents to the aqueous coating liquid as necessary, the stability and coatability of the coating liquid can be improved.

[0089] The release layer-forming composition may contain particles to prevent blocking or improve slippage, if necessary. Furthermore, the functional layer may contain an antifoaming agent, a coating improver, a thickener, an organic lubricant, an ultraviolet absorber, an antioxidant, a foaming agent, etc.

[0090] <This polyester film 10> (Thickness) The thickness of the polyester film 10 is not particularly limited as long as it is within a range that allows film formation. In particular, from the viewpoints of mechanical strength, handling properties, productivity, etc., the thickness is preferably 1 μm to 300 μm, more preferably 5 μm or more or 125 μm or less, and even more preferably 8 μm or more or 100 μm or less.

[0091] (Transmission density OD value) The polyester film 10 preferably has a transmission density OD value of 0.10 or more. A transmission density OD value of 0.10 or more means high opacity, in other words, high whiteness. From this viewpoint, the transmission density OD value of the polyester film 10 is more preferably 0.10 to 1.0, and more preferably 0.15 or more or 0.90 or less, more preferably 0.20 or more or 0.80 or less, more preferably 0.25 or more, more preferably 0.30 or more, and even more preferably 0.50 or more. If the transmission density OD value of the polyester film 10 is within the above range, the visibility, in other words, the distinguishability is good, so that the polyester film 10 can be easily peeled off after transferring the rough surface to the transfer target.

[0092] Methods for making the transmission density OD value of the present polyester film 10 0.10 or more can be, for example, by incorporating a white pigment into the polyester film base material or one of its layers, by incorporating a material having a large refractive index difference from the main component resin of the polyester film base material into the base material or a particle-containing layer, or by stretching a film containing fine particles to form voids in the polyester film base material. Among them, when whitening is achieved by including a white pigment, for example, metal compound particles, the whitening can be achieved by including metal compound particles in any one of the substrate layer, the particle-containing layer, and the layer provided on the opposite side of the substrate layer to the particle-containing layer, or in two or more of these layers. In this case, the white pigment can be exemplified by the above-mentioned particles Y having an average particle size of less than 2.0 μm.

[0093] (Film surface roughness) The average surface roughness (Ra) of the polyester film 10 is preferably 0.05 μm to 2.0 μm. Here, the average surface roughness (Ra) of the present polyester film 10 means the surface of a release layer formed on one side of the polyester film substrate, and means both surfaces of the polyester film substrate when release layers are formed on both sides of the polyester film substrate. When the average surface roughness (Ra) of the surface of the present polyester film 10 is within the above range, a matte feel can be expressed, and by pressing this surface against an object and releasing it, the matte feel can be imparted to the surface of the object. From this viewpoint, the average surface roughness (Ra) of the polyester film 10 is preferably 0.05 μm to 2.0 μm, more preferably 0.1 μm or more or 1.0 μm or less, and even more preferably 0.2 μm or more or 0.9 μm or less. The average surface roughness (Ra) of the polyester film 10 can be determined using a surface roughness measuring device, for example, a surface roughness measuring device (SE-3500) manufactured by Kosaka Laboratory Co., Ltd.

[0094] In order to set the average surface roughness (Ra) of the present polyester film 10 to 0.1 μm to 2.0 μm, for example, a particle-containing layer A is provided to set the average surface roughness (Ra) of one or both surfaces of the polyester film substrate to 0.1 μm to 2.0 μm, and the thickness of the release layer is formed sufficiently thin compared to the average surface roughness (Ra), however, the present invention is not limited to this method.

[0095] If one surface of the polyester film 10 is matte-finished, the other surface need only be roughened to an extent that does not impede handling, and does not need to be matte-finished. Therefore, the average surface roughness (Ra)1 of the particle-containing layer A side of the polyester film substrate, i.e., the surface on the release layer side, can be set to 0.1 μm to 2.0 μm, and the average surface roughness (Ra)2 of the opposite surface of the present polyester film 10 can be set to less than 0.1 μm. In this case, the ratio of (Ra)2 to (Ra)1 is preferably 0.01 to 100%, and more preferably 0.1% or more, even more preferably 1% or more, even more preferably 3% or more or 90% or less.

[0096] (Glossiness) In the present polyester film 10, the glossiness of at least the surface on the release layer side is preferably 30% or less. If the gloss of the film surface is 30% or less, it can have a luxurious matte finish, with the lower limit being about 0.1%. From this viewpoint, in the present polyester film 10, it is preferable that the gloss of at least the surface on the release layer side is 30% or less, and more preferably 0.1% or more or 30% or less, even more preferably 25% or less, and even more preferably 20% or less. The gloss of the release layer side surface of the polyester film 10 can be measured using a gloss meter. For example, the gloss can be measured using a gloss meter VG2000 manufactured by Nippon Denshoku Co., Ltd. in accordance with the method of JIS Z8741.

[0097] In the present polyester film 10, the glossiness of at least the surface on the release layer side can be adjusted to 30% or less by making the average surface roughness (Ra) of one or both surfaces of the polyester film substrate 0.05 μm to 2.0 μm and making the thickness of the release layer sufficiently thin compared to the average surface roughness (Ra), as described above, but is not limited to this method.

[0098] (Release layer peel strength) In the present polyester film 10, the peel strength of the release layer is preferably 100 to 3500 mN / cm, more preferably 500 mN / cm or more or 3000 mN / cm or less, and even more preferably 1000 mN / cm or more or 2500 mN / cm or less. By setting it in such a range, the peeling operation becomes easy. The value of the peel strength corresponds to the "peeling strength of the release layer before heating" described later. The peel strength of the release layer before heating can be measured by pressing an adhesive tape (polyester adhesive tape "No. 31B" manufactured by Nitto Denko Corporation) to the surface of the release layer once with a 2 kg rubber roller, leaving it at room temperature for 1 hour, and then peeling it at 180° using "AGX-plus" manufactured by Shimadzu Corporation at a tensile speed of 300 mm / min.

[0099] The peel strength of the release layer after heating is preferably 100 to 4500 mN / cm, more preferably 500 mN / cm or more or 3900 mN / cm or less, and even more preferably 1000 mN / cm or more or 3500 mN / cm or less. By setting the peel strength within this range, peeling can be performed sufficiently even after heating. The peeling force of the release layer after heating can be measured by pressing an adhesive tape (polyester adhesive tape "No. 31B" manufactured by Nitto Denko Corporation) on the surface of the release layer with a 2 kg rubber roller once back and forth, heating it in an oven at 100°C for 1 hour, and then leaving it at room temperature for 1 hour. The peeling force can be measured by using "AGX-plus" manufactured by Shimadzu Corporation and performing 180° peeling under the condition of a tensile speed of 300 mm / min.

[0100] In addition, in consideration of the ease of controlling the peel strength of the release layer before and after heating, the peel strength before and after heating is compared, and the value of the peel strength difference before and after heating = (peeling strength after heating - peel strength before heating) is preferably 0 to 3000 mN / cm, more preferably 0 to 2000 mN / cm, and even more preferably 0 to 1500 mN / cm.

[0101] <Method of manufacturing the polyester film 1 or 10> The following describes an example of a method for producing the polyester film 10. However, the method for producing the polyester film 10 is not limited to the method described below.

[0102] First, the raw materials for each layer, i.e., the base layer, the particle-containing layer A, the particle-containing layer B, and other layers, are prepared by a known method, and each is fed to a melt extrusion device, heated to a temperature equal to or higher than the melting point of each polymer, and melted. The molten polymer for each layer is then introduced into a die, usually via a multi-manifold or feed block, and laminated. Next, the molten sheet extruded from the die is rapidly cooled and solidified on a rotating cooling drum to a temperature below the glass transition temperature to obtain a substantially amorphous unoriented sheet. In this case, in order to improve the flatness of the sheet, it is preferable to increase the adhesion between the sheet and the rotating cooling drum, and an electrostatic application adhesion method and / or a liquid application adhesion method are preferably adopted.

[0103] Next, the obtained unstretched sheet is stretched in one direction by a roll or tenter type stretching machine. The stretching temperature is usually 70 to 150°C, preferably 80 to 140°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Next, in the direction perpendicular to the first-stage stretching direction, the sheet is stretched at usually 70 to 170°C, and the stretching ratio is usually 2.5 to 7 times, preferably 3.0 to 6 times. Subsequently, the sheet is heat-treated under tension or relaxation of 30% or less at a temperature of 180 to 270°C to obtain a biaxially oriented film. In the above stretching, a method of stretching in one direction in two or more stages can also be adopted. In that case, it is preferable to perform the stretching so that the final stretching ratios in both directions are each within the above range.

[0104] After the heat treatment step, it is preferable to relax the film by 2 to 20% in the longitudinal and / or transverse directions in the maximum temperature zone of the heat treatment and / or in the cooling zone at the heat treatment outlet. If necessary, it is also possible to add another longitudinal or transverse stretching.

[0105] In the above-mentioned production method, the release layer is preferably formed by coating the above-mentioned "release layer-forming composition" between the longitudinal stretching and the transverse stretching as the above-mentioned coating and stretching method. In this way, coating can be performed simultaneously with stretching, and the thickness of the release layer can be made thin according to the stretching ratio, so that a film suitable as a polyester film can be produced.

[0106] With respect to polyester film 1, the film thickness of polyester film 10 described above is read as the film thickness of polyester film 1, the transmission concentration OD value of polyester film 10 described above is read as the transmission concentration OD value of polyester film 1 described above, and the average surface roughness (Ra) of polyester film 10 described above is read as the average surface roughness (Ra) of polyester film 1.

[0107] The polyester film 1 and the polyester film 10 have a roughened film surface and the surface condition can be transferred to the surface of the target product, so they can be used for surface shaping applications where a matte surface is required, and are particularly suitable for use as a surface shaping film for electromagnetic wave shielding components.

[0108] <Explanation of terms> In this specification, when expressed as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when it is expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the intention that "it is preferably greater than X" or "it is preferably less than Y". EXAMPLES

[0109] The present invention will now be described in further detail with reference to the following examples and comparative examples. First, methods for measuring and evaluating various physical properties in the following examples and comparative examples will be described. In the examples and comparative examples, "parts" refers to "parts by mass." The measurement methods used in the present invention are as follows.

[0110] (1) Intrinsic viscosity of polyester 1 g of polyester from which particles incompatible with the polyester had been removed was precisely weighed, dissolved in 100 ml of a mixed solvent of phenol / tetrachloroethane = 50 / 50 (mass ratio), and measured at 30°C.

[0111] (2) Average particle size The particle size was measured by the sedimentation method using a centrifugal sedimentation type particle size distribution analyzer, SA-CP3, manufactured by Shimadzu Corporation. The average particle size was determined using the cumulative 50% (volume basis) value in the equivalent sphericity distribution of the particles obtained by the measurement.

[0112] (3) Measurement method for average surface roughness (Ra) It was determined as follows using a surface roughness measuring instrument (SE-3500) manufactured by Kosaka Laboratory Co., Ltd. That is, a portion of reference length L (2.5 mm) was cut out from the film cross-sectional curve in the direction of the average line, and the average line of this cut out portion was expressed as the x-axis and the direction of the longitudinal magnification as the y-axis, and the value given by the following formula was expressed in [nm]. The arithmetic mean roughness was expressed as the average value of the arithmetic mean roughness of the cut out portions obtained from 10 roughness curves obtained from the sample film surface. The tip radius of the stylus was 2 μm, the load was 30 mg, and the cutoff value was 0.08 mm.

[0113] Ra = (1 / L)∫L0|f(x)|dx

[0114] (4) Evaluation of gloss of polyester film The gloss was measured according to the method of JIS Z8741 using a gloss meter VG2000 manufactured by Nippon Denshoku Co., Ltd. The reflectance of the sample was determined based on the reflectance of a black standard plate at an incident angle and a reflection angle of 60 degrees, and this was taken as the gloss.

[0115] (5) Release layer thickness The surface of the release layer was stained with RuO4 and embedded in epoxy resin. Then, sections prepared by ultrathin sectioning were stained with RuO4, and the cross section of the release layer was measured using a transmission electron microscope (Hitachi High-Technologies Corporation H-7650, accelerating voltage 100 kV).

[0116] (6) Transmission density OD value According to JIS K5600-4, the transmission density of white light was measured using a Macbeth densitometer TD-904. Measurements were performed at five points, and the average value was taken as the OD value. The higher this value, the lower the light transmittance.

[0117] (7) Peel strength before heating An adhesive tape (polyester adhesive tape "No. 31B" manufactured by Nitto Denko Corporation) was pressed against the surface of the release layer with a 2 kg rubber roller, and the peel strength was measured after leaving it at room temperature for 1 hour. The peel strength was measured by peeling at 180° using "AGX-plus" manufactured by Shimadzu Corporation at a tensile speed of 300 mm / min.

[0118] (8) Peel strength after heating An adhesive tape (polyester adhesive tape "No. 31B" manufactured by Nitto Denko Corporation) was applied to the surface of the release layer by pressing it back and forth once with a 2 kg rubber roller, and then heated in an oven at 100°C for 1 hour. The tape was then left at room temperature for 1 hour, after which the peel strength was measured. The peel strength was measured using "AGX-plus" manufactured by Shimadzu Corporation, with 180° peeling at a tensile speed of 300 mm / min.

[0119] (9) Evaluation of heat resistance of release layer Using the peel strengths measured in (7) and (8) above, the difference in peel strength due to heating was calculated as follows: difference in peel strength due to heating=(peel strength after heating-peel strength before heating).

[0120] (10) Evaluation of release layer strength The release layer surface was rubbed back and forth 10 times using a rubbing tester and a special felt manufactured by Taiheirika Kogyo Co., Ltd., and then the felt was observed. Those that showed no white powder were rated as ○ (very good), those that showed only a small amount of white powder were rated as ○△ (good), those that showed some white powder were rated as △ (usual), and those that showed white powder over the entire surface were rated × (poor).

[0121] (11) Evaluation of curling The polyester film (sample) was stored in a film roll at room temperature for 24 hours and cut into a 150 mm x 150 mm sample piece for measurement. The sample piece for measurement was placed on a glass plate, and the lifting of the four corners from the glass plate was measured, and the curling was evaluated according to the following criteria. ◎ (very good): The average floating value of the four corners is 0 mm or more and less than 6 mm. ○(good): The average lift of the four corners is 6 mm or more and less than 10 mm △(usual): The average floating value of the four corners is 10 mm or more and less than 30 mm ×(poor): The average floating value of the four corners is 30 mm or more.

[0122] The polyesters used in the examples and comparative examples were prepared as follows.

[0123] <Polyester (A)> Polyethylene terephthalate homopolymer (intrinsic viscosity is 0.65 dl / g)

[0124] <Polyester (B)> Polyethylene terephthalate homopolymer containing 10% by mass of crosslinked organic particles of alkyl methacrylate-styrene copolymer with an average particle size of 4.5 μm

[0125] <Polyester (C)> Copolymerized polyethylene terephthalate with 22 mol% isophthalic acid as the dicarboxylic acid component

[0126] <Polyester (D)> Polyethylene terephthalate homopolymer containing 15% by mass of silica particles with an average particle size of 4.0 μm

[0127] <Polyester (E)> Polyethylene terephthalate homopolymer containing 15% by mass of silica particles with an average particle size of 1.5 μm

[0128] <Polyester (F)> Polyethylene terephthalate homopolymer containing 50% by mass of titanium oxide particles with an average particle size of 0.3 μm

[0129] The compounds used in forming the release layer are as follows:

[0130] <Wax emulsion (IA)> 300 g of oxidized polyethylene wax with a melting point of 140°C, 650 g of ion-exchanged water, 50 g of decaglycerin monooleate surfactant, and 10 g of 48% potassium hydroxide aqueous solution were added to a 1.5 L emulsification equipment equipped with a stirrer, thermometer, and temperature controller, and the contents were replaced with nitrogen. The equipment was then sealed and stirred at high speed at 150°C for 1 hour, cooled to 130°C, and passed through a high-pressure homogenizer at 400 atmospheric pressure and cooled to 40°C to obtain a wax emulsion (IA).

[0131] <Wax emulsion (IB)> Wax emulsion (IB) was obtained in the same manner as in the production method of wax emulsion (IA) except that paraffin wax having a melting point of 60°C was used.

[0132] <Long-chain alkyl compounds (IC)> 200 parts of xylene and 600 parts of octadecyl isocyanate were added to a four-neck flask and heated under stirring. From the point when xylene started to reflux, 100 parts of polyvinyl alcohol with an average degree of polymerization of 500 and a degree of saponification of 88 mol% were added in small portions at 10-minute intervals over about 2 hours. After the addition of polyvinyl alcohol was completed, the mixture was refluxed for another 2 hours to terminate the reaction. The reaction mixture was cooled to about 80°C and then added to methanol, whereupon the reaction product precipitated as a white precipitate. The precipitate was filtered off, 140 parts of xylene was added, heated to completely dissolve the product, and then methanol was added again to cause precipitation. This operation was repeated several times, and the precipitate was washed with methanol, dried, and pulverized to obtain a long-chain alkyl compound (IC).

[0133] <Fluorine compounds (ID)> In a glass reaction vessel, 80.0 g of a perfluoroalkyl group-containing acrylate, CF3(CF2)nCH2CH2OCOCH=CH2 (n = 5 to 11, average of n = 9), 20.0 g of acetoacetoxyethyl methacrylate, 0.8 g of dodecyl mercaptan, 354.7 g of deoxygenated pure water, 40.0 g of acetone, and C 16 H 33 1.0g of N(CH3)3Cl and C8H17 C6H4O(CH2CH2O) n 3.0 g of H (n=8) was added, and 0.5 g of azobisisobutylamidine dihydrochloride was added. The mixture was subjected to copolymerization reaction at 60° C. for 10 hours with stirring under a nitrogen atmosphere to obtain a copolymer emulsion of a fluorine compound (ID).

[0134] <Melamine compounds (IIA)> Hexamethoxymethylolmelamine

[0135] <Isocyanate compounds (IIB)> 1000 parts of hexamethylene diisocyanate was stirred at 60°C, and 0.1 parts of tetramethylammonium caprylate was added as a catalyst. After 4 hours, 0.2 parts of phosphoric acid was added to stop the reaction, and an isocyanurate-type polyisocyanate composition was obtained. 100 parts of the obtained isocyanurate-type polyisocyanate composition, 42.3 parts of methoxypolyethylene glycol having a number average molecular weight of 400, and 29.5 parts of propylene glycol monomethyl ether acetate were charged and kept at 80°C for 7 hours. Thereafter, the reaction liquid temperature was kept at 60°C, and 35.8 parts of methyl isobutanoyl acetate, 32.2 parts of diethyl malonate, and 0.88 parts of a 28% methanol solution of sodium methoxide were added, and the mixture was kept for 4 hours. 58.9 parts of n-butanol was added, and the reaction liquid temperature was maintained at 80° C. for 2 hours. Thereafter, 0.86 parts of 2-ethylhexyl acid phosphate was added to obtain an isocyanate compound (IIB) as a blocked polyisocyanate.

[0136] <Polyester resin (III)> Aqueous dispersion of polyester resin copolymerized in the following ratios: (acid components) terephthalic acid / isophthalic acid / 5-sodium sulfoisophthalic acid / / (diol components) ethylene glycol / 1,4-butanediol / diethylene glycol = 56 / 40 / 4 / / 70 / 20 / 10 (mol%).

[0137] [Example 1] A raw material mixture of polyesters (B) and (C) in mass ratios of 80% and 20%, respectively, was used as the raw material for layer A (particle-containing layer A), polyester (A) was used as the raw material for the base layer, and a raw material mixture of polyesters (A), (E), and (F) in mass ratios of 70%, 15%, and 15%, respectively, was used as the raw material for layer B (particle-containing layer B). Each of these was supplied to three extruders and melted at 285°C. Then, the resulting materials were co-extruded onto a cooling roll set at 35°C in a layer structure of three types and three layers (layer A / base layer / layer B = extrusion rate of 5:40:5), and the materials were cooled and solidified to obtain an unstretched sheet. Next, the film was stretched 3.0 times in the longitudinal direction at a film temperature of 85°C using the difference in roll peripheral speed, and then coating solution 1 shown in Table 1 below was applied to the A layer surface of this longitudinally stretched film, which was then introduced into a tenter and stretched 4.1 times in the transverse direction at 95°C. After heat treatment at 235°C, the film was relaxed by 2% in the transverse direction to obtain a polyester film (sample) having a release layer with a film thickness of 0.03 μm after drying on the A layer side of the polyester film base material with a thickness of 50 μm (A layer / base layer / B layer = 5 μm / 40 μm / 5 μm) and an average surface roughness (Ra) of the release layer side surface of 0.6 μm. The properties of this polyester film (sample) are shown in Table 2 below.

[0138] [Examples 2 to 12] A polyester film (sample) was obtained in the same manner as in Example 1, except that the composition of the coating solution was changed to the composition shown in Table 1. The properties of the obtained polyester film (sample) are shown in Table 2. The polyester films (samples) of all the Examples had good average surface roughness (Ra) and glossiness, and the difference in peel force before and after heating and the strength of the release layer were also good.

[0139] [Example 13] The layer B (particle-containing layer B) was made from a mixture of polyesters (A), (B), (C), and (F) in mass ratios of 65%, 10%, 10%, and 15%, respectively, and the layer B was made from coating solution 5 shown in Table 1 below, instead of coating solution 1. Except for this, the layer B was made from a polyester film substrate having a thickness of 50 μm (layer A / substrate layer / layer B=5 μm / 40 μm / 5 μm), and the layer A was made from a polyester film substrate having a thickness of 50 μm (layer A / substrate layer / layer B=5 μm / 40 μm / 5 μm). The layer A side had a release layer with a thickness of 0.03 μm after drying, and the average surface roughness (Ra) of the release layer side surface was 0.6 μm. The properties of this polyester film (sample) are shown in Table 3 below.

[0140] [Example 14] The raw material of layer A (particle-containing layer A) was a mixture of polyesters (A) and (D) at a mass ratio of 65% and 35%, respectively, and the raw material of layer B (particle-containing layer B) was a mixture of polyesters (A) and (D) at a mass ratio of 85% and 15%, respectively. Each was fed to three extruders, melted at 285°C, and then co-extruded onto a cooling roll set at 40°C in a layer configuration of three types and three layers (A layer / base layer / B layer = 5:40:5 discharge amount), and cooled and solidified to obtain an unstretched sheet. The manufacturing process was the same as in Example 1, and a polyester film (sample) was obtained in which a release layer with a film thickness of 0.03 μm after drying was formed on the A layer side of a polyester film substrate with a thickness of 50 μm (A layer / base layer / B layer = 5 μm / 40 μm / 5 μm), and the average surface roughness (Ra) of the release layer side surface was 0.4 μm. The properties of this polyester film (sample) are shown in Table 2 below.

[0141] [Examples 15 to 25] A polyester film (sample) was obtained in the same manner as in Example 14, except that the composition of the coating solution was changed to the composition shown in Table 1. The properties of the obtained polyester film (sample) are shown in Table 2. The polyester films (samples) of all the Examples had good average surface roughness (Ra) and glossiness, and the difference in peel force before and after heating and the strength of the release layer were also good.

[0142] [Comparative Example 3] The same production process as in Example 14 was carried out except that a mixture of polyesters (A) and (E) in mass ratios of 65% and 35%, respectively, was used as the raw material for layer A (particle-containing layer A), polyester (A) was used as the raw material for the base layer, and coating liquid 5 shown in Table 1 below was applied instead of coating liquid 1. A polyester film (sample) was obtained, which had a release layer with a dry thickness of 0.03 μm on the layer A side of the polyester film base material with a thickness of 50 μm (layer A / base layer / layer B = 5 μm / 40 μm / 5 μm) and an average surface roughness (Ra) of the release layer side surface of 0.2 μm. The properties of this polyester film (sample) are shown in Tables 2 and 3 below. The film had high gloss and poor visibility.

[0143] [Comparative Example 4] The raw material for layer A (particle-containing layer A) was a mixture of polyesters (A) and (B) at a mass ratio of 20% and 80%, respectively, and the raw material for layer B (particle-containing layer B) was a mixture of polyesters (A), (B) and (F) at a mass ratio of 90%, 8% and 2%, respectively. Each was fed to two extruders, melted at 285°C, and then co-extruded onto a cooling roll set at 40°C in a layer structure of two types and two layers (A layer / B layer = 5:45 extrusion amount), and cooled and solidified to obtain an unstretched sheet. The manufacturing process was the same as in Example 1, except that an unstretched sheet was obtained by cooling and solidifying the unstretched sheet. A polyester film (sample) was obtained, which had a release layer with a film thickness of 0.03 μm after drying on the A layer side of a polyester film substrate with a thickness of 50 μm (A layer / B layer = 5 μm / 45 μm), and had an average surface roughness (Ra) of 0.5 μm on the release layer side surface. The properties of this polyester film (sample) are shown in Table 3 below, and the film had poor curling properties.

[0144] [Table 1]

[0145] [Table 2]

[0146] [Table 3]

[0147] Table 2 above demonstrates the first and second polyester films of the present invention, and Table 3 above demonstrates the third polyester film of the present invention.

[0148] From the results of the above examples and the results of tests conducted by the inventors thus far, it has been found that if the transmission density OD value of a polyester film is 0.10 or more, the visibility of the polyester film during transfer can be excellent. It was also found that by forming a particle-containing layer containing particles having an average particle size of 2.0 μm or more on one or both sides of a base layer, and further forming a release layer on the surface of the particle-containing layer, the polyester film surface can be suitably roughened and the desired matte feel can be transferred to an object. [Industrial Applicability]

[0149] The polyester film 10 has excellent visibility during transfer, in other words, excellent distinguishability, and has a roughened film surface. Therefore, even when a release layer is formed, the roughened state is not smoothed out, and the desired matte feel can be imparted to the target object. Therefore, the polyester film 10 can be suitably used for applications in which a matte surface is transferred to the target object, in particular as a polyester film for surface shaping of electromagnetic wave shielding components. [Explanation of symbols]

[0150] 1: Polyester film 11: Polyester film base 111: Base material layer 112: Particle-containing layer A 113: Release layer

Claims

1. A polyester film substrate comprising a particle-containing layer A on one side of the substrate layer, the particle-containing layer A containing particles with an average particle size of 3.0 μm or more, and a particle-containing layer B on the other side of the substrate layer, the particle-containing layer B containing particles with an average particle size of less than 2.0 μm but not containing particles with an average particle size of 2.0 μm or more, and a release layer on the surface of the particle-containing layer A; The average surface roughness (Ra) of the release layer side surface is 0.4 μm to 2.0 μm, A polyester film having a transmission density OD value of 0.25 or more.

2. The polyester film according to claim 1, wherein the release layer contains a release agent and a crosslinking agent, and the proportion of the crosslinking agent in the release layer forming composition that forms the release layer is 40 mass % or less of the non-volatile components of the release layer forming composition.

3. 3. The polyester film according to claim 1 or 2, wherein the polyester film substrate is a stretched polyester film substrate.

4. The polyester film according to any one of claims 1 to 3, which is used for transferring a surface state of the polyester film to a surface of an object by contacting the surface of the polyester film with the surface of the object and pressing the surface of the object to be adhered thereto, and then peeling the polyester film off.

5. 5. The polyester film according to claim 1, wherein the gloss of the surface on the release layer side is 30% or less.

6. 6. The polyester film according to claim 1, wherein the particles having an average particle size of 3.0 μm or more are organic particles.

7. 7. The polyester film according to claim 1, wherein the particles having an average particle size of 3.0 μm or more are silica particles.

8. The polyester film according to any one of claims 1 to 7, wherein the release layer has a crosslinked structure derived from a crosslinking agent.

Citation Information

Patent Citations

  • Antistatic polyester film

    JP1996169096A

  • Mold releasing film

    JP2001293835A

  • Laminated polyester film

    JP2014012372A

  • Polyester film for in-mold transfer

    JP2014024341A

  • Laminated polyester film

    JP2014210906A